2004
DOI: 10.1177/1534734604271031
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Evaluation of Pterocarpus santalinus Linn. Ointment on Lower Extremity Wounds—A Preliminary Report

Abstract: Pterocarpus santalinus is described in the Ayurveda for its wide spectrum of medicinal properties including wound healing. Previously the authors reported animal studies that demonstrated that an ointment made from the bark of this tree was effective without any toxic effects. They used the same ointment in 6 cases of lower extremity wounds. Healing was observed in all wounds. The study was not controlled, the findings are presented here as case studies. Further studies are planned to develop a wound healing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Due to the mentioned effects, the tincture has a longstanding use as an aid in healing of minor wounds. 118 Animal studies and case studies [126][127][128] Not in wound care…”
Section: Seedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the mentioned effects, the tincture has a longstanding use as an aid in healing of minor wounds. 118 Animal studies and case studies [126][127][128] Not in wound care…”
Section: Seedsmentioning
confidence: 99%
“…Liquid extracts (ethanol), gels and ointments Allergic dermatitis 125 Animal studies and case studies [126][127][128] Not in wound care Description: Pterocarpus santalinus (Family: Fabaceae). The wood of the red sanders is traditionally used due to astringent and tonic properties.…”
Section: Leaves Flowermentioning
confidence: 99%
“…Wounds treated with the test ointment healed far more quickly, therefore, Pterocarpus santalinus is safe and effective for animal models [100]. Moreover, in using the previous study, they were using the ointment to 6 lower extremity wound patients and recorded [103]. Wound healing was observed when the ointment was tested [103].…”
Section: Pterocarpus Santalinus Linnmentioning
confidence: 99%
“…Moreover, in using the previous study, they were using the ointment to 6 lower extremity wound patients and recorded [103]. Wound healing was observed when the ointment was tested [103]. Impacts on hematology metrics are provided to demonstrate the changes, but they cannot make meaningful inferences from these observations [103].…”
Section: Pterocarpus Santalinus Linnmentioning
confidence: 99%
“…The results were finally quantified by PAGE study with estimation of protein synthesis in which it was found that proteins with different molecular weight on the variations in different days were synthesised indicating its potentiality in triggering the cell signalling system for successful healing of the wounds. A pilot clinical study on selected six patients of lower extremity wounds was evaluated with 15% paste of the drug under ointment base and significant (p < 0.01) improvement was observed (Figure 2) on the basis of the granulation and epithelialisation [22]. The drug has been patented officially and now being marketed either as single ingredient or in combined form for the purpose of wound healing.…”
Section: Pterocarpus Santalinusmentioning
confidence: 99%